Openness and Industrial Response in a Wal-Mart World: A Case Study of Mexican Soaps, Detergents and Surfactant Producers - Javorcik, Beata; Keller, Wolfgang; Tybout, James (World Bank, Washington, DC, 2012)
This paper uses a case study approach to explore the effects of NAFTA and GATT membership on innovation and trade in the Mexican soaps, detergents, and surfactants (SDS) industry. Several basic findings emerge. First, the most fundamental effect of the NAFTA and the GATT on the SDS industry was to help induce Wal-Mart to enter Mexico. Once there, Walmex fundamentally changed the retail sector, forcing SDS firms to cut their profit margins and innovate. Those unable to respond to this new environment tended to lose market share and, in some cases, disappear altogether. Second, partly in response to Walmex, many Mexican producers logged impressive efficiency gains during the previous decade. These gains came both from labor-shedding and from innovation, which in turn was fueled by innovative input suppliers and by multinationals bringing new products and processes from their headquarters to Mexico. Finally, although Mexican detergent exports captured an increasing share of the U.S. detergent market over the past decade, Mexican sales in the U.S. were inhibited by a combination of excessive shipping delays at the border and artificially high input prices (due to Mexican protection of domestic caustic soda suppliers). They were also held back by the major re-tooling costs that Mexican producers would have had to incur to establish brand recognition among non-Latin consumers and to comply with zero phosphate laws in many regions of the U.S.